Variability of the Coupling Between Surface Air Temperature and Northern Annular Mode at Various Levels - Tan Benkui; Suo Lingling; Huang Jiayou (acta meteorologica sinica, 2008)
This article focuses on the variability of the coupling between surface air temperature (SAT) and northern annular mode (NAM) at various levels. To measure the coupling intensity between the SAT and the NAM anomaly fields, the coupling index has been defined as the leading principal component of the partial least squares regression model of the SAT and NAM anomalies. Both a composite analysis and the coupling index have been used to reveal level-by-level and month-to-month variability of the coupling between the tipper anomalous NAM and the SAT in the Northern Hemisphere. The major results are as follows: the January SAT anomaly is more strongly coupled with the January NAM anomaly at the middle-upper tropospheric levels than that at the other levels, while the same is true for the February SAT anomaly with the January NAM anomaly at the lower stratospheric levels. The January NAM anomaly at the middle-upper tropospheric levels is most strongly coupled with the January SAT anomaly, and the coupling intensity is successively reduced month by month and becomes trivial after April. The January NAM anomaly at the lower stratospheric levels is more strongly coupled with January, February and March SAT anomalies, but the coupling becomes trivial after April. Meteorology & Atmospheric Sciences SCI(E) 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 0 ARTICLE 3 277-283 22